2020
DOI: 10.1186/s12957-020-01909-5
|View full text |Cite
|
Sign up to set email alerts
|

Combining texture features of whole slide images improves prognostic prediction of recurrence-free survival for cutaneous melanoma patients

Abstract: Background: Accurate prediction of recurrence-free survival (RFS) is important for the prognosis of cutaneous melanoma patients. The image-based pathological examination remains as the gold standard for diagnosis. It is of clinical interest to account for computer-aided processing of pathology image when performing prognostic analysis. Methods: We enrolled in this study a total of 152 patients from TCGA-SKCM (The Cancer Genome Atlas Skin Cutaneous Melanoma project) with complete information in recurrence-relat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
(23 reference statements)
1
5
0
Order By: Relevance
“…Pathology imaging provides an important view of cancer tissue and has been widely used in diagnosing primary and metastatic cancers [ 67 , 68 , 69 ]. Eight cell types were segmented and counted from the pathology images and the percentage of each cell type among all the detected cells was denoted as the image feature of this cell type for the corresponding sample.…”
Section: Resultsmentioning
confidence: 99%
“…Pathology imaging provides an important view of cancer tissue and has been widely used in diagnosing primary and metastatic cancers [ 67 , 68 , 69 ]. Eight cell types were segmented and counted from the pathology images and the percentage of each cell type among all the detected cells was denoted as the image feature of this cell type for the corresponding sample.…”
Section: Resultsmentioning
confidence: 99%
“…The post-surgery evaluation of disease-free survival outcome has gained increasing attention for management of melanoma patients in consequence of the continuous progress in defining even more suitable therapies during the last few years. Whether WSI analysis can improve the prediction of prognostic tasks related to melanoma with respect to considering clinical data alone is currently under scrutiny within the scientific community [23][24][25]31,32 . As example, Peng et al 31 developed lasso Cox prediction models based on the integration of clinical variables, gene signature and WSI features to predict recurrence-free survival in melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Whether WSI analysis can improve the prediction of prognostic tasks related to melanoma with respect to considering clinical data alone is currently under scrutiny within the scientific community [23][24][25]31,32 . As example, Peng et al 31 developed lasso Cox prediction models based on the integration of clinical variables, gene signature and WSI features to predict recurrence-free survival in melanoma patients. The integration of WSI features with baseline clinical variable improved performance obtained by using clinical variable only.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, we plan to include more types of data, and we are particularly interested in the whole slide images (WSIs). Studies ( Cheerla and Gevaert, 2019 ; Peng et al., 2020 ) have demonstrated that WSI data alone, as well as together with genomic data, can achieve a remarkable performance in cancer prognosis prediction. However, most pancreatic cancer-specific studies using WSI data focused on diagnosis, i.e., pancreatic cancer detection and segmentation ( Fu et al., 2021 ; Kriegsmann et al., 2021 ; Le et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%